Enhancing plant disease diagnostics in the Pacific - Hofer, Katharina M.; Toome-Heller, Merje; Alexander, Brett J.R. (New Zealand Plant Protection, 2019)
A project aiming to enhance biosecurity and market access in the Pacific was launched by NZ Aid in 2016. The project intends to benefit the economies of New Zealand’s Pacific neighbours by improving their biosecurity systems which, in turn, would help to protect New Zealand’s borders. Under the current project, the MPI’s Plant Health and Environment Laboratory (PHEL) is accountable for delivering insect pest and disease diagnostic training in the Pacific and developing diagnostic tools. The PHEL Mycology and Bacteriology team has delivered a number of plant pathology training sessions in New Zealand, Cook Islands and Fiji. The main focus of the pathology module was to provide the Biosecurity Authority of Fiji (BAF) Plant Health Laboratory staff with skills and tools to conduct plant disease diagnostics at their facility. This included a full laboratory refurbishment and new molecular setup. As a result, the BAF team has become efficient with isolating and identifying plant pathogens using a combination of morphology and DNA-based approaches. They are now able to provide fast and sensitive testing for high impact diseases at the border or in future incursions. In addition to laboratory staff training, a number of quarantine officers were trained to enable them to recognise diseased plant material during import and export fresh produce inspections.